1986
DOI: 10.1007/bf02556591
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 1,25 dihydroxycholecalciferol on parathyroid hormone secretion by monolayer cultures of bovine parathyroid cells

Abstract: Controversy exists over a direct effect of 1,25(OH)2D3 on PTH secretion. To investigate the possibility that the suppressive effect of 1,25(OH)2D3 on PTH secretion may be demonstrable in 1,25(OH)2D3-depleted tissue and/or after prolonged periods of exposure to 1,25(OH)2D3, primary monolayer cultures of bovine parathyroid cells were established in 1:1 DMEM/Ham's F-12 media supplemented with 2% calf serum but not 1,25(OH)2D3. Ionized calcium was maintained at 1.0 mM. Experiments were performed on 4-day-old cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…An alternative explanation for the increase in PTH with age might stem from findings that altered vitamin D metabolism could modulate iPTH levels. It was reported that parathyroid cells exposed to 1,25-dihydroxycholecalciferol had a significantly decreased rate of PTH secretion due to declines in the steady state level of prepro-PTH mRNA and the rate of PTH gene transcription (60)(61)(62). Decreased suppression would be consistent with previous findings of a lower concentration of the vitamin D metabolite in aged rats (63) and a decreased renal 1-a hydroxylase activity in mitochondria from the 24 mo animal (64).…”
Section: Discussionsupporting
confidence: 85%
“…An alternative explanation for the increase in PTH with age might stem from findings that altered vitamin D metabolism could modulate iPTH levels. It was reported that parathyroid cells exposed to 1,25-dihydroxycholecalciferol had a significantly decreased rate of PTH secretion due to declines in the steady state level of prepro-PTH mRNA and the rate of PTH gene transcription (60)(61)(62). Decreased suppression would be consistent with previous findings of a lower concentration of the vitamin D metabolite in aged rats (63) and a decreased renal 1-a hydroxylase activity in mitochondria from the 24 mo animal (64).…”
Section: Discussionsupporting
confidence: 85%
“…According to the results shown in Fig. 1 Several studies suggest that 1 ,25(OH)2D3 directly inhibits the secretion of PTHfrom the parathyroid glands (22)(23)(24)(25) and also suppresses the production of PTHmRNA in parathyroid glands, independent of the concentration of ionized Ca (26)(27)(28). In the present study, the weekly administration of 8.0 |Ug of 1,25(OH)2D3 suppressed the PTH level without elevating the serum Ca.…”
Section: Discussionsupporting
confidence: 64%
“…[Ca ion ] may fall because increased phosphate will decrease the physicochemical driving forces for bone mineral dissolution (21) and favor ectopic precipitation of Ca phosphate complexes (90). In addition, phosphate retention will directly decrease serum 1,25(OH) 2 (99,(102)(103)(104)(105). In addition, during renal failure, there is decreased binding of 1,25(OH) 2 D 3 to the parathyroid cells (106).…”
Section: Ckd In Patients Who Are Not On Dialysismentioning
confidence: 99%